Birleşme, Bölünme, Tür Değiştirme ve İşletme Devrindeİşçiyi Koruyan Hükümler ve İş Kanunu HükümlerininDeğerlendirilmesi - (:unkn) unknown (My University, 2019)
Ticaret şirketleri, işletme ve işyerlerinin birleşme, bölünme, tür değiştirme ve devri işlemlerininiş sözleşmeleri üzerindeki etkisi inceleme konusuyapıldığında, konunun, Borçlar Kanunu, Türk Ticaret Kanunu ve İş Kanunu yönünden incelenmesibir zorunluluk olarak ortaya çıkmaktadır.Gerçekten de her üç kanundaki konuya ilişkindüzenlemeler incelendiğinde, söz konusu mevzuatın birbiriyle uyumlu olmadığı gibi boşluk doldurma düşüncesi ile de hazırlanmadıkları anlaşılmaktadır.Bu nedenle, aşağıda, bahse konu hukuki işlemlerin iş sözleşmeleri üzerindeki etkisi ve buna bağlıolarak da her üç Kanundaki konuya ilişkin düzenlemelerin hangi hallerde uygulanacağı incelemekonusu yapılacaktır

When the effects of merger, division, type change and transfer operations of trading companies, business enterprises and workplaces are examined, it is essential that this topic should be examined in terms of Turkish Code of Obligations, Turkish Commercial Code and Labour Law. Indeed, when the regulations in all these three laws related to these issues are examined, it is understood that these regulations are not compatible with each other and they are not prepared with the idea of filling the gap. For this reason, the impact of the legal transactions mentioned above on the employment contracts and under which conditions the regulations of these three laws shall be applicable related to these issues will be the subject of the evaluations.
Provisions Protecting Workers in Merger Divisions, Type Change and Operation Transfer and Evaluation of Provisions of Labor Law